1999
DOI: 10.1152/jappl.1999.87.2.484
|View full text |Cite
|
Sign up to set email alerts
|

Changes in respiratory timing induced by hypercapnia in maturing rats

Abstract: Premature infants respond to hypercapnia by an attenuated ventilatory response that is characterized by a decrease in respiratory frequency. We hypothesized that this impaired hypercapnic ventilatory response is of central origin and is mediated via gamma-aminobutyric acid-ergic (GABAergic) pathways. We therefore studied two groups of maturing Sprague-Dawley rats: unrestrained rats in a whole body plethysmograph at four postnatal ages (5, 16-17, 22-23, and 41-42 days); and ventilated, decerebrate, vagotomized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 37 publications
(42 reference statements)
3
18
0
Order By: Relevance
“…Early reports indicated that the hypercapnic response was very modest in the first 2 postnatal weeks (Bamford et al, 1996). There was little effect of CO 2 on frequency early in development (VT did increase), but the frequency response increased by P18, and the development of an increased ventilatory response to CO 2 over the first weeks of life tracked the emergence of a frequency response to CO 2 (Bamford et al, 1996;Abu-Shaweesh et al, 1999). Stunden et al (2001) described changes in ventilation during hypercapnia in neonatal rats ranging in age from P1 to P21 and in animals greater than 100 days of age.…”
Section: The Acute Response To Hypercapniamentioning
confidence: 99%
See 1 more Smart Citation
“…Early reports indicated that the hypercapnic response was very modest in the first 2 postnatal weeks (Bamford et al, 1996). There was little effect of CO 2 on frequency early in development (VT did increase), but the frequency response increased by P18, and the development of an increased ventilatory response to CO 2 over the first weeks of life tracked the emergence of a frequency response to CO 2 (Bamford et al, 1996;Abu-Shaweesh et al, 1999). Stunden et al (2001) described changes in ventilation during hypercapnia in neonatal rats ranging in age from P1 to P21 and in animals greater than 100 days of age.…”
Section: The Acute Response To Hypercapniamentioning
confidence: 99%
“…However, there are conflicting reports about whether or not GABA is excitatory early in development. Some investigators have interpreted the poor frequency response to inhaled CO 2 in the early postnatal period as evidence of inhibitory GABAergic effects, since bicuculline, a GABA A antagonist, enhanced the frequency response to CO 2 even in P5 rats (Abu-Shaweesh et al, 1999). Furthermore, Kim et al (1997) showed that GABA occasionally depolarizes rostral NTS neurons from young rats, while Grabauskas and Bradley (2001) found that rostral NTS neurons from young rats hyperpolarized in the same manner as adult neurons in response to GABA.…”
Section: Maturation Of 'Inhibitory' Chemical Synapses-mentioning
confidence: 99%
“…The ventilatory response to a single hypercapnic exposure has been extensively studied and is diminished in apneic preterm infants [2,3] and during early postnatal life in both preterm infants and rat pups [4][5][6] . The characteristic increase in tidal volume is accompanied by a decrease in respiratory frequency during hypercapnic exposure in preterm infants [7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…Based upon these data, it is possible that a maturation of hypothalamic circuits could contribute to changes in respiratory regulation that occur during the first week of development of the rat (28). It is known that levels of arcuate neurotransmitters do not reach adult levels until several weeks after birth (29).…”
Section: Discussionmentioning
confidence: 99%